An introduction to Russian literature - Butler-Booker, Sandra; White, Edmund; Guidance Associates (Mount Kisco, N.Y.: Guidance Associates, 1975)
Views Russian history from the early nineteenth century to the present through the eyes of some of its major writers.
Photographer, Ron Tunison ; illustrator, Guy Smalley ; consultants, Shirlee Neil and Dr. Juan Alonso.
DVD format.
Keywords: Russian literature -- History and criticism